Additive manufacturing of metal matrix composites via nanofunctionalization. (21st May 2018) - Martin, John H.; Yahata, Brennan D.; Clough, Eric C.; Mayer, Justin A.; Hundley, Jacob M.; Schaedler, Tobias A.
Abstract: Abstract : A novel, alloy-agnostic, nanofunctionalization process has been utilized to produce metal matrix composites (MMCs) via additive manufacturing, providing new geometric freedom for MMC design. MMCs were produced with the addition of tungsten carbide nanoparticles to commercially available AlSi10Mg alloy powder. Tungsten carbide was chosen due to the potential for coherent crystallographic phases that were identified utilizing a lattice-matching approach to promote wetting and increase dislocation interactions. Structures were produced with evenly distributed strengthening phases leading to tensile strengths >385 MPa and a 50% decrease in wear rate over the commercially available AlSi10Mg alloy at only 1 vol% loading of tungsten carbide.